Spanish Version of the Short Grit Scale (Grit-S): New evidence based on CFA and MIRT models in Peruvian University Students - Yupanqui-Lorenzo, Daniel E.; Becerra-Herrera, Wilson A.; Diaz-Leon, Ivan; Cardoza Sernaqué, Manuel Antonio; Olivera-Carhuaz, Edith S. (Revista Fuentes, 2024)
Studying grit’s measurement helps to understand this psychological phenomenon associated with success. Grit-S structures of one-factor and two-factor have been reported in the literature, but there is a lack of reports by IRT models. Therefore, two objectives were proposed: to determine the factorial structure of the Spanish version of the Grit-S and explore the instrument through a MIRT analysis. A nonprobabilistic sample of 899 subjects (41.0% female) was evaluated. The Grit-S instrument, composed of eight items, was used. The CFA showed that the two-factor model obtained a good fit (χ2[df] = 140.6 [19], CFI = 0.97, TLI = 0.95, RMSEA [90%CI] = 0.08 [0.07, 0.10], SRMR = 0.04) unlike the one-dimensional model. An exploratory comparison analysis by MIRT also revealed that the two-factor model performed better (p < 0.001). Consequently, a confirmatory analysis determined an adequate fit of the two-factor model (C2 = 45.4, df = 13, p < 0.001; RMSEA [90%CI] = 0.05 [0.04 - 0.07]; SRMSR = 0.05; TLI = 0.97; CFI = 0.99). Multidimensional discrimination values were within the expected range (> 1; > 1.5), although item 2 had low discrimination. Regarding difficulty, all items had a monotonic increase. The two-factor model fits the data by both CFA and MIRT. Both complementary analyzes demonstrate the potential of Grit-S to measure latent consistency and perseverance factors.